2015
DOI: 10.1039/c4tb01522c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired passive anti-biofouling surfaces preventing biofilm formation

Abstract: Our bioinspired, superhydrophobic surfaces show exceptional ability to passively inhibit the biofilm formation of Gram-positive and Gram-negative bacteria over a 7 day period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…[ 46 ] Owing to their biodegradability, the superhydrophobic coatings may potentially be a platform for preparing a temporary anti-biofouling coating for surgical instruments. More [ 47] They demonstrated that the wax modified surfaces passively (with no toxic influence on bacterial cells) inhibited the formation of biofilms (reduction of 95.6-99.9% over a 7 day period) by B. cereus and P. aeruginosa. Importantly, the wax surfaces can be formed on a variety of materials and intricately shaped surfaces, showing potentially feasible for various medical and industrial applications.…”
Section: Bioinspired Superhydrophobic Surfacesmentioning
confidence: 99%
“…[ 46 ] Owing to their biodegradability, the superhydrophobic coatings may potentially be a platform for preparing a temporary anti-biofouling coating for surgical instruments. More [ 47] They demonstrated that the wax modified surfaces passively (with no toxic influence on bacterial cells) inhibited the formation of biofilms (reduction of 95.6-99.9% over a 7 day period) by B. cereus and P. aeruginosa. Importantly, the wax surfaces can be formed on a variety of materials and intricately shaped surfaces, showing potentially feasible for various medical and industrial applications.…”
Section: Bioinspired Superhydrophobic Surfacesmentioning
confidence: 99%
“…The underwater oleophobicity is to be distinguished from the in-air oleophobicity which stands for resistance to oil adhesion in air. Inspired by biological surfaces such as sharkskin and clamshells that are resistant to biological or organic adhesion underwater, the materials science community has developed a plethora of interfacial materials with underwater superoleophobicity for different applications such as marine biofouling control [21,22] and oil-water separations [23][24][25][26][27][28][29][30][31][32][33]. In general, there are two requirements for constructing an underwater superoleophobic surface: rough (textured) surface morphology and hydrophilic surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…3D crystalline wax surfaces form a heterogeneous surface that combines wax and air pockets, reducing the contact area between a bacterial cell and the surface and thereby interrupting bacterial adhesion, thus preventing the initial step of biofilm formation (Pechook et al, 2015).…”
Section: Biofilm Control Strategiesmentioning
confidence: 99%